Attracting the heart : social relations and the aesthetics of emotion in Sri Lankan monastic culture - Samuels, Jeffrey, 1965- (Topics in contemporary Buddhism., 2010)
An ethnographic study done in Sri Lanka that examines how emtion comes into play in the commitments of laypeople and monastics to each other and to Buddhism.